Clinical and morphological evaluation of snake venom derived fibrin glue on the tendon healing in dogs - Ferraro, G. C. [UNESP]; Moraes, J. R. E. [UNESP]; Pereira, G. T. [UNESP]; Moraes, F. R. [UNESP]; Bueno De Camargo, M. H. [UNESP] (Centro de Estudos de Venenos e Animais Peçonhentos, 2005)
The aim of this study was to evaluate the effect of snake venom derived fibrin glue on the healing of the deep digital flexor tendon, during three periods. The tendon of the 2nd digit of 30 thoracic limbs of dogs was partially sectioned for glue application. Biopsies were performed 7, 15, and 30 days post surgery for the clinical and morphological study of tendons. Analysis of the results showed that 73.3% of the tendons showed stump retraction and 16.6% moderate to excessive adherence, which affected sliding. There was a significant difference in the number of inflammatory cells among the three studied periods, being the highest on day 15. The morphological analysis revealed a typical tendon healing process with a lower level of inflammation in the acute phase, facilitating the cicatricial maturation phase. Snake venom derived fibrin glue promotes the healing in dog flexor tendon.
Keywords: dog; fibrin glue; snake venom; healing; tendon